2009
DOI: 10.1111/j.1440-1746.2009.05863.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with transarterial chemoembolization and interferon‐α compared with transarterial chemoembolization alone for hepatitis B virus related unresectable hepatocellular carcinoma

Abstract: IFN-alpha treatment reduced recurrence and improved the survival of patients after TACE treatment of HBV-related HCC, with acceptable toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…In the only study that reported median PFS and OS in our systematic review, there is a statistically significant survival benefit for adding antiviral treatment to TACE (p = 0.003) [14]. Alternatively, in the study by Gao et al, the intrahepatic tumour recurrence rate at 1 and 2 years in the TACE + IFN group was 16.1% and 29.0%, compared with 38.7% and 61.3% in the TACE group (p < 0.05).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the only study that reported median PFS and OS in our systematic review, there is a statistically significant survival benefit for adding antiviral treatment to TACE (p = 0.003) [14]. Alternatively, in the study by Gao et al, the intrahepatic tumour recurrence rate at 1 and 2 years in the TACE + IFN group was 16.1% and 29.0%, compared with 38.7% and 61.3% in the TACE group (p < 0.05).…”
Section: Discussionmentioning
confidence: 68%
“…All patients had intermediate-stage or advanced HCC that was not amenable to liver resection or transplantation. Only four out of the five trials have reported on the severity of liver disease using the Child-Pugh classification system [12][13][14][15]. The majority of patients (58.3-100%) exhibited Child-Pugh class A severity of disease, indicating well-compensated disease.…”
Section: Patient Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Eight studies [30], [34], [37][41], [43] aimed to investigate the effect of adjuvant IFN on HCC patients after curative treatment with surgical resection or local ablation therapy. Five [32], [33], [35], [36], [42] studies evaluated the effect of IFN on intermediate and advanced HCC patients. Eleven RCTs studied in Asian populations.…”
Section: Resultsmentioning
confidence: 99%
“…IFN-α-2b also failed to decrease the risk of postoperative recurrence [18] . In contrast, interferon showed some benefits when combined with other modalities such as chemotherapy, curative resection and TACE [19][20][21][22] . Two meta-analyses revealed that adjuvant interferon therapy after curative therapy for HCC could improve both overall survival and recurrence-free survival [23,24] .…”
Section: Cytokinesmentioning
confidence: 99%